2022
DOI: 10.32604/iasc.2022.020235
|View full text |Cite
|
Sign up to set email alerts
|

A Modelling and Scheduling Tool for Crowd Movement in Complex Network

Abstract: Managing events pose a unique challenge to the stakeholders and authorities to control the crowd in all three phases of the event (pre, during and post), ensuring crowd safety. One of the fundamental keys to provide crowd safety is to consider the mobility infrastructure hosting the crowd, i.e., routes, areas, entrances and exits. During Hajj, where millions of pilgrims worldwide fulfil the annual event's rites, mina encampment incorporates pilgrims performing recurring stoning ritual conducted over multi-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Several research endeavors have been conducted in recent decades on different aspects of applications and challenges in large-scale Islamic religious gatherings. Some recent research can be found in the literature including those by Ahmad et al (2018); Alshammari et al (2021); Felemban et al (2020Felemban et al ( , 2022; Sindia et al (2022); Shambour (2021). Airports designed to accommodate large numbers of Muslims are among the most critical stations through which Muslims pass to perform their religious activities.…”
Section: Related Workmentioning
confidence: 99%
“…Several research endeavors have been conducted in recent decades on different aspects of applications and challenges in large-scale Islamic religious gatherings. Some recent research can be found in the literature including those by Ahmad et al (2018); Alshammari et al (2021); Felemban et al (2020Felemban et al ( , 2022; Sindia et al (2022); Shambour (2021). Airports designed to accommodate large numbers of Muslims are among the most critical stations through which Muslims pass to perform their religious activities.…”
Section: Related Workmentioning
confidence: 99%
“…Train location and bus movements were tracked through GPS and used to build the platform. The same author recently proposed a novel modeling tool for scheduling crowd movement in Mina [263]. Also targeting crowd evacuation plans, Alqurashi and Altman proposed an agent-based framework that is multi-level and multi-stage to automate the decision-making process in case of emergency [264].…”
Section: G Crowd Managementmentioning
confidence: 99%